The Influence of Leadership Style and Compensation on Employee Engagement and Turnover Intention in Indonesian Textile Company - Sitorus, Danyo Rakhmada (Cv. Syntax Corporation Indonesia, 2025)
The focus of this research is to analyze and determine the influence and impact of leadership style and compensation on employee engagement and turnover intentions at CV XYZ, a small and medium-sized textile organization operating in Indonesia. The background and importance of conducting this research are influenced by the turnover intent rate in the organization of 21.05 percent per year, which is mainly related to compensation and leadership. The research with a sequential explanatory research design and combining qualitative and quantitative methods will be conducted by involving 32 employees and interviews with nine respondents. The findings have clearly shown that transformational and transactional leadership styles have a positive relationship with employee engagement and a negative relationship with employee turnover intention. However, laissez-faire leadership styles have a negative relationship with employee engagement and a positive relationship with employee turnover intentions. Fair and transparent compensation practices have been shown to have a significant impact on motivation and engagement and are an important determinant in influencing employee turnover intentions. Qualitative findings have supported these findings and point to contradictions related to leadership styles among divisions and perceptions related to workload and rewards. This research adds value to the existing literature because it illustrates the understanding in the textile industry and the relationship between leadership and compensation and employee engagement. This research recommends developing relationships with leadership, compensation based on fairness, and creating employee engagement programs.